Aspectos nutricionais de farinhas de vísceras de aves e sua utilização em rações de frangos de corte - Da Silva, Edney Pereira [UNESP]; De Lima, Michele Bernardino; Rabello, Carlos Boa-Viagem; Ludke, Jorge Vitor; Albino, Luiz Fernando Teixeira; Sakomura, Nilva Kazue [UNESP] (My University, 2011)
In the process of slaughtering chickens, parts of them are discarded because are unfit for human consumption. These wastes should be directed to a destination that does not promote any risk to the environment and above all, according with the laws regulating waste disposal. So, the wastes are transformed into byproducts for utilization in the animal nutrition, poultry and swine feeding, but cannot use for ruminant feed, only non-ruminant feeding. In Brazil, the first scientific studies on the use of by-products of poultry slaughter as a protein source in diets for broiler chickens were started in the 1960's, and these results were used for a long time for food formulation, but the need to improve the herds stimulated the search for improvement in technologies for more accurate diet formulations. The objective of this article is to review some aspects of the physic-chemical composition, energy values and their use in diets for broilers.
Nutritional aspects of poultry offal meal and its use for broiler chicken feeding
Keywords: Alternative feed; Animal by-product meals; Broiler chickens; Animalia; Bovidae; Gallus gallus; Suidae